Copper(ii) gluconate (a non-toxic food supplement/dietary aid) as a precursor catalyst for effective photo-induced living radical polymerisation of acrylates1. Issue 19 (21st May 2015) - Nikolaou, Vasiliki; Anastasaki, Athina; Alsubaie, Fehaid; Simula, Alexandre; Fox, David J.; Haddleton, David M.
<x xml:space="preserve">Abstract</x> Copper gluconate, is employed as a precursor catalyst for the photo-induced living radical polymerisation of acrylates.